Investigation of piezoelectric actuation effect on fracture toughness of isotropic materials - Hrairi, Meftah (2019)
In this study, the active repair and control of a Mode-I opening displacement for centre/edge cracked structures is conducted. The repair and control technique is performed utilizing the piezoelectric electromechanical behaviour. The study is divided into two major parts whereas accurate mathematical models are proposed. The models relate the Mode-I stress intensity factor and piezoelectric actuator parameters for centre and edge cracked isotropic plates respectively. The electromechanical models are based on Linear Elastic Fracture Mechanics (LEFM), the virtual crack closure method, the singular stress at the crack tip, and the coupling effects of the piezoelectric actuator. In addition, the superposition method is applied for the stress intensity factor produced by the piezoelectric actuator as the only external load on the cracked plate and the stress intensity factor due to the far field tension load. The proposed analytical models are then verified by finite element analysis (FEA). The results demonstrate a good agreement between the analytical and finite element models. The work then proceeds by conducting experimental investigations in order to validate the proposed analytical model and the finite element analysis. The experimental results show that the proposed analytical solution is applicable with reasonable accuracy. Moreover, a parametric study is conducted to understand the influence and study the efficiency of the piezoelectric actuator on mitigation of the Mode-I SIF. The parametric results indicate that the applied voltage, actuator shape, and thickness have significant influence on the active repair performance. In summary, this project has demonstrated the feasibility and practicality of the active repair of the edge/centre cracked isotropic plate under Mode-I loading using analytical, numerical simulations, and experimental studies.